Harmful practices prevail despite legal knowledge: a mixed-method study on the paradox of child marriage in Bangladesh - Akter, Sayema; Williams, Chloe; Talukder, Animesh; Islam, Muhammed Nazmul; Escallon, Juanita Vasquez; Sultana, Tania; Kapil, Neha; Sarker, Malabika (Sexual and reproductive health matters, 2021)
Child marriage is a globally recognised human rights violation that disproportionately affects girls, especially in developing countries. It has serious negative consequences on girls’ physical, mental, sexual, and reproductive health and rights. Although well-pronounced laws against child marriage were enacted in Bangladesh, the practice remains a significant challenge. Lack of law enforcement and persistent social norms ultimately allow child marriage to persist around the country. Social norms have an impact on the prevalent attitudes toward child marriage. Therefore, this mixed-method study aimed to explore the legal knowledge, perception, and practice of child marriage in Bangladesh. This study was part of a broader evaluation of a UNICEF media programme. Adolescent boys and girls aged between 10 and 19 years and their parents were interviewed in three Bangladeshi districts. All the respondents were aware of the legal age of marriage and knew that child marriage is punishable by law. This study illuminated the reasons, including early marriage among boys, poverty, dowry, and sexual harassment. Communities and policymakers need to be engaged to trigger larger structural and cultural changes to remedy the harmful social norm and its practice.